Discharge breastmilk feeding rates in asymptomatic term newborns admitted to the neonatal intensive care unit for maternal chorioamnionitis. (18th August 2019) - Shim, Miry; Yang, Sara; Messina, Catherine R.; Mintzer, Jonathan P.
Abstract: Purpose: To compare discharge breastmilk feeding rates among asymptomatic term newborns receiving 48-hour versus >48-hour antibiotics in the neonatal intensive care unit (NICU) and a cohort of well-baby nursery (WBN) newborns. Materials and methods: This retrospective review included asymptomatic term neonates admitted to the NICU due to maternal chorioamnionitis and a comparison group of WBN neonates between January 2012 and December 2015. Demographic, birth, feeding, and lactation consultant visit data were analyzed in univariate and multivariate models. Results: Among 272 NICU neonates, 237 (87%) received 48-hour antibiotics versus 35 (13%) who received >48-hour (h) antibiotics; a cohort of 428 WBN neonates was studied for comparison. Exclusive breastmilk feeding was seen in 14% of NICU versus 35% of WBN neonates ( p < .01). Among NICU newborns, 48 h versus >48 h antibiotics was not associated with altered discharge breastmilk feeding (14 versus 14%; p = .89). On multivariate logistic regression analysis among NICU subjects, older maternal age ( p < .01), lower parity ( p = .02), first-feed breastmilk ( p < .01), and more lactation consultant visits ( p = .012) were associated with increased discharge breastmilk feeding. Conclusions: NICU admission for presumed early-onset sepsis due to maternal chorioamnionitis was associated with reduced discharge breastmilk feeding in asymptomatic term neonates, but prolonged antibiotic exposure was not. We speculate that demographic factors, such as maternal age and parity, may aid in focusing lactation consultant efforts to potentially improve NICU exclusive discharge breastmilk feeding rates.